Peningkatan Hasil Belajar Bahasa Indonesia pada Peserta Didik Menggunakan Model Problem Based Learning (PBL) di Kelas IV SDN 28 Pasar Rabaa Kabupaten Agam - Putri, Amelisa Maha; Desyandri, Desyandri (COGNITIVISM: Journal of Educational Research and Development, 2025)
This research aims to describe how the improvement of student learning outcomes in Indonesian language learning on the Procedural Text material using the Problem Based Learning (PBL) model in the 4th grade of SDN 28 Pasar Rabaa, Agam Regency. This type of research is action research (PTK) using both qualitative and quantitative approaches. The research was conducted over two cycles, with the research procedure consisting of planning, implementation, observation, and reflection. The research data obtained relates to the learning outcomes of the Problem Based Learning (PBL) model. Data collection techniques included tests and non-tests. The subjects of this research are the classroom teacher as the observer, the researcher as the practitioner or teacher, and the 20 students of the 4th grade at SDN 28 Pasar Rabaa, Agam Regency. The research results show that the teaching module in cycle I achieved an average of 85.4% (B), which increased in cycle II to 95.8% (SB). The results of the implementation of the teacher's aspect in cycle I achieved an average of 82.14% (B), which increased in cycle II to 96.42% (SB). The results of the implementation of the students' aspect in cycle I achieved an average of 82.14% (B), which increased in cycle II to 96.42% (SB). The students' learning outcomes in cycle I achieved an average of 76.37% (C), which increased in cycle II to 89.5% (B)